Not-sew-wicked stepmom. 5 - Iru (Graphic novelist); Mo9Rang (Graphic novel illustrator) (Not-sew-wicked stepmom, 2024)
As the Freidkin family prepares for the Queen Mother's return, they're filled with dread and anticipation--until the woman arrives, and she actually seems...nice? Abigail's first impressions of Sabrian's mother are hardly what she was expecting, but that doesn't mean she'll let her guard down. When she senses a change in Blanche's behavior, Abigail begins to suspect something is off, and her suspicions are confirmed when she learns of the Queen Mother's plans to marry off her stepdaughter!